Minimally Invasive Oral and Maxillofacial Surgery (Springer Berlin Heidelberg, 2018)
Minimally invasive techniques, designed to reduce morbidity and risk while simultaneously improving outcomes, are increasingly being used in oral and maxillofacial surgery. This book covers the most recent technological developments and the advanced techniques used when performing such minimally invasive surgery in patients with common and rare oral and maxillofacial pathologies. The relevant basic science is reviewed, but the principal focus is on the surgical techniques themselves. These are described step by step with the aid of numerous superb color illustrations that will help the clinician to gain a full understanding of the technology and the procedures. In addition, still emerging techniques of endoscopy, navigation, and minimally invasive surgery are well covered. This text will be a premier resource for physicians who diagnose and treat oral and maxillofacial pathologies and injuries.